Politics and the histories of international law: the quest for knowledge and justice - Schäfer, Raphael; Peters, Anne (Brill Nijhoff, 2021)
What are the implications of writing the history of legal issues? Eighteen authors from different legal systems and backgrounds offer different answers, by examining the history writing on issues ranging from slavery over the use of force to extraterritorial jurisdiction. Contributions show how historiography has often distorted or neglected regional cultures and suggest alternative methods and approaches to history writing. These studies are highly relevant for current international relations in which the fight over master narratives is especially fierce among governments, in different academic fields, and also between governments and academics
Keywords: Aufsatzsammlung; Geschichte; Politik; Völkerrecht